Assessment of retinal pigment epithelial cells in epiretinal membrane formation. Issue 6 (June 2015) - Wang, Lei‐Chi; Hung, Kuo‐Hsuan; Hsu, Chih‐Chien; Chen, Shih‐Jen; Li, Wing‐Yin; Lin, Tai‐Chi
Abstract : Background : The definite etiology of epiretinal membrane (ERM) is unknown. Clinically, ERM may cause metamorphopsia and decreased vision during the disease exacerbation. Several theories of pathogenesis emphasize a glial tissue origin. However, in some studies, surgically removed ERM specimens were found to contain retinal pigment epithelial (RPE) cells. The actual mechanism by which RPE cells gain access into the inner retina and what roles they play in the formation of ERM remain controversial. The purpose of this study was to evaluate the incidence of RPE cells in ERM and discuss the possible mechanisms. Methods : A retrospective review of the histological findings in 23 surgically removed specimens of ERM was done. The samples were studied using light microscopy and immunohistochemistry. Results : Glial cells were the main components in all 23 cases, and RPE cells were found in five of the specimens. Two of these five cases were clinically diagnosed as idiopathic macular pucker, whereas the other three cases were identified as macular pucker associated with previous retinal detachment. A much higher density of myofibroblasts was noted in these five specimens than in the other 18 cases. Conclusion : The incidence of RPE cells found in ERM is 21.7% (5 out of 23 specimens). A strong association between RPE cells and myofibroblasts in cases of ERM with or without retinal detachment indicates that RPE cells may contribute to the formation of ERM via a wound healing process.